Análisis semiótico-jurídico entre el poder moral y el poder ciudadano: Semiotic-Legal Analysis Between Moral Power and Citizen Power - Cedeño Román, Joel Evelio; Calderón , Carlos Alberto (Universidad del Zulia, 2021)
The present investigation carries out a legal-semiotic analysis of the Moral Power as a Bolivarian proposal in the Constitution of 1819 and the Citizen Power present in the Constitution of the Bolivarian Republic of Venezuela 1999. It seeks to identify influences and determinations. The importance for the republican development of a legal entity in charge of ensuring ethical education is highlighted; as well as, the surveillance and control over public administrators. The rescue and determinations of the Bolivarian proposal are concluded in the Magna Carta currently in force. It is a bibliographic investigation of a legal nature from the rationalist-deductive approach.